The Impact of Self-Management on the Quality of Life of Patient with Diabetes Mellitus: A Systematic Review - Sukma Wicaturatmashudi; Pradana Soewondo; Debie Dahlia; Sali Rahadi Asih; Dewi Gayatri; Ratna Aryani (Universitas Airlangga, 2024)
Background: Diabetes mellitus is a hereditary and degenerative disease that requires management throughout the patient's life to maintain blood sugar stability and psychosocial factors. Aims: This systematic review aims to determine the effect of self-management on the quality of life of patients with Type 2 DM. Methods: The selection of the studies refers to Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines and JBI's checklist was used to assess the quality of the study. The study selection came from 7 databases Scopus, ScienceDirect, Sage Journals, ProQuest, Emerald Insight, Pubmed dan Taylor & Francis. The number of studies included in the review was 7 articles, 5 articles used an RCT design, and 2 articles were quasi-experimental. Results: The finding showed 2 articles that provide interventions in the form of DSME, 1 article emphasizes self-management interventions based on self-efficacy theory that is oriented towards active family involvement, 1 article specifies interprofessional-based DSM through telemonitoring media, 1 article focuses on community-based self-management interventions, and 1 article specializes in the use of weblogs in conducting self-management. Special 2 articles emphasize nurse leadership in managing interventions during the study. Five articles showed a significant effect of self-management on quality of life and 2 articles had no effect. Conclusion: The findings can be used to optimize self-management intervention in DM patients to improve their quality of life.